A stable manganese-based halide with narrow-band green light emission and its preparation method and application

By using 4-butylamine-7-chloroquinoline as a ligand, a narrow half-maximum width, high color purity and stable green light-emitting manganese-based halide was prepared, which solved the problems of material stability and cost in the prior art, and achieved widespread application in optical devices.

CN118580186BActive Publication Date: 2025-04-15JINING UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410620673.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-20
Publication Date
2025-04-15
Estimated Expiration
2044-05-20

AI Technical Summary

Technical Problem

In the prior art, β-SiAlON:Eu(II) green phosphor has limited its wide application due to its expensive raw materials and harsh synthetic conditions; at the same time, the poor chemical stability of quantum dots also limits its application. Therefore, it is necessary to explore novel stable fluorescent materials with narrow bandwidth and high photoluminescent quantum yields.

Method used

Using 4-butylamine-7-chloroquinoline as ligand, a narrow half-maximum width, high color purity and stable green light-emitting manganese-based halide (C13H16ClN2)2MnX4, X is Cl or Br. This method is simple and green, and improves the stability of the material by controlling the crystal structure.

Benefits of technology

A narrow band green light emission was achieved, with a half-maximum width of 55nm and 39nm, respectively, and has high corrosion resistance to polar organic solvents and acidic solutions, and maintains good stability under atmospheric exposure, light and heating conditions. This material is used in optical devices, especially in white LEDs, and has the characteristics of a wide color gamut and high working stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118580186B_ABST
    Figure CN118580186B_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of luminescent materials, and specifically relates to a stable manganese-based halide emitting narrow-band green light, a preparation method and an application thereof. 4-butylamino-7-chloroquinoline is used as a ligand, and a solvent evaporation method is adopted to prepare a green light emitting manganese-based halide with narrow half-peak width, high color purity and high stability. The preparation method is simple and green. The prepared manganese-based halide is applied to optical devices, such as white light LEDs, and has the characteristics of wide color gamut and high working stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of luminescent materials, and in particular relates to a stable manganese-based halide emitting narrow-band green light, and a preparation method and application thereof. Background Art

[0002] In the past few decades, β-SiAlON:Eu(II) green phosphors have been used to assemble light-emitting diodes (LEDs) due to their high photoluminescence quantum yield (PLQY) (52.2%) and narrow half-width (55nm). However, the extremely expensive raw materials and harsh synthesis conditions severely limit the widespread application of β-SiAlO:Eu(II). In addition, researchers have also constructed various light-emitting semiconductor quantum dots (QDs) with extremely narrow half-width. However, the poor chemical stability of these quantum dots also limits their application. Therefore, there is a need to further explore new stable fluorescent materials with narrow bandwidths.

[0003] Manganese (Mn 2+ )-based halides have obvious advantages because of their tetrahedral [MnX4] 2- The unit has an almost constant green emission. The concentration of manganese in the earth's crust is about 0.1%, ranking 12th in abundance, and it is a cheap raw material. In addition, low toxicity makes Mn 2+ Low-dimensional metal halides (LDMHs) have broad application prospects.

[0004] However, there is still a need to further explore manganese-based hybrid metal halides with the combined advantages of narrow bandwidth and high PLQY. Summary of the invention

[0005] In order to solve the problems raised by the background technology, the present invention provides a stable manganese-based halide with narrow-band green light emission and a preparation method and application thereof.

[0006] The technical solution of the present invention is as follows:

[0007] The present invention provides a stable manganese-based halide with narrow-band green light emission.

[0008] The manganese-based halide is (C 13 H 16 ClN2)2MnX4, where (C 13 H 16 ClN2) + is a 1-hydrogen-4-butylamino-7-chloroquinoline cation, and X is Cl or Br;

[0009] The 13 H 16 ClN2)2MnCl4 belongs to the monoclinic system, with a space group of C2 / c;

[0010] The 13 H 16 ClN2)2MnBr4 belongs to the triclinic system, with space group Pī;

[0011] In the manganese-based halide, all Mn 2+ All of them are coordinated with four halogen atoms to form 0D[MnX4] 2- Tetrahedral structure.

[0012] The 13 H 16 ClN2)2MnCl4, emits 526nm green light under 369nm ultraviolet light excitation, with a half-peak width of 55nm;

[0013] The 13 H 16 ClN2)2MnBr4, emits 519nm green light under 370nm ultraviolet light excitation, and the half-peak width is 39nm. The present invention also provides a method for preparing the stable manganese-based halide emitting narrow-band green light, comprising the following steps:

[0014] (1) Synthesis of 4-butylamino-7-chloroquinoline: Under nitrogen protection, 4,7-dichloroquinoline and n-butylamine were mixed, heated to reflux and then cooled, sodium hydroxide solution was added, stirred, and the precipitated solid was filtered, washed, dried, and purified to obtain 4-butylamino-7-chloroquinoline;

[0015] (2) Preparation of manganese-based halide: a manganese-containing halide, 4-butylamino-7-chloroquinoline, propylene glycol and an acidic solvent are uniformly mixed, and after the solvent evaporates, crystals are precipitated, which are washed and dried to obtain a manganese-based halide.

[0016] In the step (2), a manganese-based halide is prepared,

[0017] If the manganese-based halide is (C 13 H 16 ClN2)2MnCl4, then the manganese-containing halide is manganese chloride and the acidic solvent is hydrochloric acid;

[0018] If the manganese-based halide is (C 13 H 16 ClN2)2MnBr4, the manganese-containing halide is manganese bromide and the acidic solvent is hydrobromic acid.

[0019] In the step (2), the molar ratio of the manganese halide to 4-butylamino-7-chloroquinoline is 1:2; the volume ratio of propylene glycol to the acidic solvent is 4:3; and the molar ratio of the manganese halide to the acidic solvent is 0.2 mmol:72 mmol.

[0020] The present invention also provides the application of the stable manganese-based halide emitting narrow-band green light or the manganese-based halide prepared by the preparation method in fluorescent materials.

[0021] The application is the application of manganese-based halides in optical devices.

[0022] The manganese-based halide is used to improve the color gamut and stability of optical devices.

[0023] Beneficial Effects

[0024] The invention uses 4-butylamino-7-chloroquinoline as a ligand and adopts a solvent evaporation method to prepare a green light emitting manganese-based halide with narrow half-peak width, high color purity and high stability, and the preparation method is simple and green;

[0025] The manganese-based halide of the present invention has high corrosion resistance to polar organic solvents and acidic solutions; and still has good stability under atmospheric exposure, light, and heating conditions; (C 13 H 16 ClN2) + The π…π stacking and CH…π hydrogen bonding of cations promote the rigidity of the crystal structure, which is beneficial to narrow-band emission and crystal stability;

[0026] The present invention applies the prepared manganese-based halide to optical devices, such as white light LEDs, which have the characteristics of wide color gamut and high working stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 Schematic diagram of the structure, wherein (a) is 4-butylamino-7-chloroquinoline, and (b) is 1-hydrogen-4-butylamino-7-chloroquinoline cation.

[0028] Figure 2 Powder X-ray diffraction patterns of different crystals, where (a) is (BACQ)2MnCl4 crystal and (b) is (BACQ)2MnBr4 crystal.

[0029] Figure 3The fluorescence properties of the (BACQ)2MnCl4 crystal of Example 1 and the (BACQ)2MnBr4 crystal of Example 2 at 300K are characterized, wherein (a) is the (BACQ)2MnCl4 crystal without ultraviolet irradiation, (b) is the (BACQ)2MnCl4 crystal irradiated with 365nm ultraviolet irradiation, (c) is the (BACQ)2MnBr4 crystal without ultraviolet irradiation, and (d) is the (BACQ)2MnBr4 crystal irradiated with 3 Under 65nm ultraviolet irradiation, (e) is the excitation and emission spectra of (BACQ)2MnCl4 crystal, (f) is the excitation and emission spectra of (BACQ)2MnBr4 crystal, (g) is the CIE coordinates of (BACQ)2MnCl4 crystal, (h) is the CIE coordinates of (BACQ)2MnBr4 crystal, (i) is the attenuation curve of (BACQ)2MnCl4 crystal, and (j) is the attenuation curve of (BACQ)2MnBr4 crystal.

[0030] Figure 4 The photoluminescence quantum yield diagram of different crystals at room temperature, where (a) is (BACQ)2MnCl4 crystal and (b) is (BACQ)2MnBr4 crystal.

[0031] Figure 5 The optical characterization and stability of the (BACQ)2MnCl4 crystal of Example 1 under different treatment conditions, wherein (a) is the luminescence of the (BACQ)2MnCl4 crystal immersed in different organic solvents and concentrated hydrochloric acid; (b) is the fluorescence spectrum of the (BACQ)2MnCl4 crystal immersed in different organic solvents and concentrated hydrochloric acid; (c) is the fluorescence spectrum of the (BACQ)2MnCl4 crystal immersed in concentrated hydrochloric acid; (d) is the fluorescence spectrum of the (BACQ)2MnCl4 crystal immersed in different organic solvents and concentrated hydrochloric acid. (e) is the fluorescence spectrum of (BACQ)2MnCl4 crystals in a laboratory environment exposed to the atmosphere for 30 days; (f) is the fluorescence spectrum of (BACQ)2MnCl4 crystals after 48 hours of light exposure; (g) is the powder X-ray diffraction pattern of (BACQ)2MnCl4 crystals in a laboratory environment exposed to the atmosphere for 30 days, 48 ​​hours of light exposure and heating at 150°C for 48 hours; (h) is the fluorescence spectrum of (BACQ)2MnCl4 crystals after heating at 150°C for 48 hours.

[0032] Figure 6The half-peak width and stability of the crystal are analyzed, where (a) is the emission spectrum of (BACQ)2MnCl4 crystal with temperature change, (b) is the emission spectrum of (BACQ)2MnBr4 crystal with temperature change, (c) is the photo of (BACQ)2MnCl4 crystal and (BACQ)2MnBr4 crystal from 80K to room temperature under 365nm ultraviolet excitation, (d) is [BACQ] + Schematic diagram of the π…π bond of a cation, (e) is [BACQ] + Schematic diagram of the CH…π bond of the cation, (f) is the two-dimensional fingerprint of (BACQ)2MnBr4, (g) is the Hirshfeld surface map of the (BACQ)2MnBr4 crystal, and (h) is a schematic diagram of the total energy framework of the (BACQ)2MnBr4 crystal along the c-axis.

[0033] Figure 7 Applications of (BACQ)2MnBr4 crystals, where (a) is a schematic diagram of the luminescence characteristics of LEDs based on (BACQ)2MnBr4 crystals, (b) is the CIE coordinates of LEDs based on (BACQ)2MnBr4 crystals, (c) is the emission spectrum of LEDs based on (BACQ)2MnBr4 crystals at different operating currents, (d) is the linear relationship between the intensity of the emission spectrum and the operating current, (e) is the stability of LEDs based on (BACQ)2MnBr4 crystals, and (f) is a schematic diagram of polymer film luminescence based on (BACQ)2MnBr4 crystals. DETAILED DESCRIPTION

[0034] The following examples are intended to illustrate the present invention rather than to further limit the present invention.

[0035] The present invention provides a stable manganese-based halide with narrow-band green light emission.

[0036] The manganese-based halide is (C 13 H 16 ClN2)2MnX4, where (C 13 H 16 ClN2) + is 1-hydrogen-4-butylamino-7-chloroquinoline cation, denoted as [BACQ] + , the structure is as follows Figure 1 As shown in (b), X is Cl or Br;

[0037] The 13 H 16 ClN2)2MnCl4 belongs to the monoclinic system, with a space group of C2 / c;

[0038] The 13 H 16ClN2)2MnBr4 belongs to the triclinic system and has a space group of Pī.

[0039] All Mn in the manganese-based halide of the present invention 2+ All of them are coordinated with four halogen atoms to form 0D[MnX4] 2- Tetrahedral structure.

[0040] In addition, in the narrow-band green emission, the (C 13 H 16 ClN2)2MnCl4, emits 526nm green light under 369nm ultraviolet light excitation, with a half-peak width of 55nm;

[0041] The 13 H 16 ClN2)2MnBr4, emits 519nm green light under 370nm ultraviolet light excitation, and the half-peak width is 39nm. The present invention also provides a method for preparing the stable manganese-based halide emitting narrow-band green light, comprising the following steps:

[0042] (1) Synthesis of 4-butylamino-7-chloroquinoline: Under nitrogen protection, 4,7-dichloroquinoline and n-butylamine were mixed, heated to reflux and then cooled, sodium hydroxide solution was added, stirred, and the precipitated solid was filtered, washed, and dried to purify 4-butylamino-7-chloroquinoline, the structure of which is shown in FIG. Figure 1 As shown in (a);

[0043] (2) Preparation of manganese-based halide: a manganese-containing halide, 4-butylamino-7-chloroquinoline, propylene glycol and an acidic solvent are uniformly mixed, and after the solvent evaporates, crystals are precipitated, which are washed and dried to obtain a manganese-based halide.

[0044] The invention uses 4-butylamino-7-chloroquinoline as a ligand and adopts a solvent evaporation method to prepare a green light emitting manganese-based halide with narrow half-peak width, high color purity and high stability, and the preparation method is simple and green.

[0045] Preferably, in step (2), a manganese-based halide is prepared.

[0046] If the manganese-based halide is (C 13 H 16 ClN2)2MnCl4, then the manganese-containing halide is manganese chloride and the acidic solvent is hydrochloric acid;

[0047] If the manganese-based halide is (C 13 H 16 ClN2)2MnBr4, the manganese-containing halide is manganese bromide and the acidic solvent is hydrobromic acid.

[0048] In addition, in the step (2), the molar ratio of the manganese-containing halide to 4-butylamino-7-chloroquinoline is 1:2; the volume ratio of propylene glycol to the acidic solvent is 4:3; and the molar ratio of the manganese-containing halide to the acidic solvent is 0.2 mmol:72 mmol.

[0049] The present invention also provides an application of the stable manganese-based halide emitting narrow-band green light or the manganese-based halide prepared by the preparation method in fluorescent materials, especially in optical devices, which is manifested in the application of the manganese-based halide in improving the color gamut and stability of optical devices. For example, the manganese-based halide is applied to white light LEDs, which have the characteristics of wide color gamut and high working stability.

[0050] The drugs and reagents used in the following experiments were of analytical grade.

[0051] Example 1

[0052] (1) Synthesis of 4-butylamino-7-chloroquinoline: Under nitrogen protection, 10 g of 4,7-dichloroquinoline and 40 mL of n-butylamine were mixed and added to a 100 mL round-bottom flask, heated under reflux at 100° C. for 12 h, then cooled, 50 mL of 2 mol / L sodium hydroxide solution was added, stirred for 5 min, the precipitated solid was filtered, washed, dried, and purified by column chromatography to obtain 4-butylamino-7-chloroquinoline;

[0053] (2) Preparation (C 13 H 16 ClN2)2MnCl4: 0.2mmol of MnCl2·4H2O (0.0396g), 0.4mmol of 4-butylamino-7-chloroquinoline (0.0992g), 8mL of propylene glycol and 6mL of concentrated hydrochloric acid were mixed evenly, dissolved with ultrasound assistance and evaporated naturally. Crystals were precipitated after 4 days, washed with ethanol and dried to obtain manganese halide (C 13 H 16 ClN2)2MnCl4, denoted as (BACQ)2MnCl4.

[0054] Example 2

[0055] (1) Synthesis of 4-butylamino-7-chloroquinoline: Under nitrogen protection, 10 g of 4,7-dichloroquinoline and 40 mL of n-butylamine were mixed and added to a 100 mL round-bottom flask, heated under reflux at 100° C. for 12 h, then cooled, 50 mL of 2 mol / L sodium hydroxide solution was added, stirred for 5 min, the precipitated solid was filtered, washed, dried, and purified by column chromatography to obtain 4-butylamino-7-chloroquinoline;

[0056] (2) Preparation (C 13 H 16ClN2)2MnBr4: 0.2mmol of MnBr2·4H2O (0.0574g), 0.4mmol of 4-butylamino-7-chloroquinoline (0.0992g), 8mL of propylene glycol and 6mL of hydrobromic acid were mixed evenly, dissolved by ultrasound and evaporated naturally, and crystals were precipitated after 4 days. After washing with ethanol and drying, manganese halide (C 13 H 16 ClN2)2MnBr4, denoted as (BACQ)2MnBr4.

[0057] Experimental Results

[0058] 1. Crystal structure

[0059] The crystal structures of the (BACQ)2MnCl4 crystals of Example 1 and the (BACQ)2MnBr4 crystals of Example 2 were analyzed by powder X-ray diffraction. Figure 1 , as shown in Table 1.

[0060] The results show that (BACQ)2MnCl4 crystals are monoclinic with centrosymmetric space group C2 / c, (BACQ)2MnBr4 crystals are triclinic with space group Pī, and all Mn 2+ All of them are coordinated with four halogen atoms to form 0D[MnX4] 2- Tetrahedral structure.

[0061] Table 1 Crystal structure data of (BACQ)2MnCl4 and (BACQ)2MnBr4

[0062]

[0063]

[0064] Note: a R1=(Σ||F o |-|F c ||) / Σ|F o |. b wR2={Σw(F o 2 -F c 2 ) 2 / ΣwF o 2} 1 / 2 .

[0065] 2. Crystal fluorescence properties

[0066] In order to study the fluorescence properties of the (BACQ)2MnCl4 crystal of Example 1 and the (BACQ)2MnBr4 crystal of Example 2, fluorescence, color coordinates, lifetime, and photoluminescence quantum yield (PLQY) tests were carried out respectively.

[0067] First, use 365nm ultraviolet light to preliminarily detect the luminescence effect of the crystal. Figure 3 It can be seen from (a), (b), (c) and (d) that at an ambient temperature of 300K, (BACQ)2MnCl4 crystals and (BACQ)2MnBr4 crystals can both emit high-intensity green light under 365nm ultraviolet light.

[0068] Depend on Figure 3 As shown in (e) and (f), (BACQ)2MnCl4 crystal and (BACQ)2MnBr4 crystal exhibit similar excitation (PLE) and emission (PL) spectra. The photoluminescence spectra of the two crystals have three main peaks near 285, 370 and 450 nm. 13 H 16 ClN2)2MnCl4 crystal emits 526nm green light under 369nm ultraviolet light excitation, with a half-peak width of 55nm ( Figure 3 (e)); (C 13 H 16 ClN2)2MnBr4 crystal emits 519nm green light under 370nm ultraviolet light excitation, with a half-peak width of 39nm ( Figure 3 (f) in the figure.

[0069] Depend on Figure 3 From (g) and (h) in the figure, we can see that (C 13 H 16 ClN2)2MnCl4 crystals and (C 13 H 16 The International Commission on Illumination (CIE) coordinates of ClN2)2MnBr4 crystals are (0.27, 0.62) and (0.17, 0.72), respectively, which are close to the CIE coordinates of traditional green light (0.21, 0.71).

[0070] Depend on Figure 3 From the attenuation curves (i) and (j), we can see that (C 13 H 16 ClN2)2MnCl4 crystals and (C 13 H 16 The lifetimes of ClN2)2MnBr4 crystals are 1.406ms and 0.1173ms respectively.

[0071] In addition, the photoluminescence quantum yield (PLQY) of (BACQ)2MnCl4 crystals and (BACQ)2MnBr4 crystals was also measured at room temperature in order to accurately determine the emission efficiency. Figure 4 It can be seen that the PLQY of (BACQ)2MnCl4 crystal and (BACQ)2MnBr4 crystal are 36% and 48% respectively.

[0072] Furthermore, the half-peak width, lifetime, and photoluminescence quantum yield (PLQY) of (BACQ)2MnCl4 and (BACQ)2MnBr4 crystals were compared with those of other Mn 2+ The organic-inorganic metal halides were compared, as shown in Table 2.

[0073] Table 2 Mn of different cations 2+ Comparison of organic and inorganic metal halides

[0074]

[0075] It can be seen from Table 2 that compared with the existing Mn 2+ Compared with the organic-inorganic metal halide, the (BACQ)2MnCl4 crystal of Example 1 and the (BACQ)2MnBr4 crystal of Example 2 have a narrower half-peak width, especially the (BACQ)2MnBr4 crystal. In addition, the (BACQ)2MnCl4 crystal of Example 1 and the (BACQ)2MnBr4 crystal of Example 2 also have certain advantages in terms of lifetime and photoluminescence quantum yield (PLQY).

[0076] 3. Crystal stability

[0077] In order to prove that the crystal has good stability, the (BACQ)2MnCl4 crystal of Example 1 was selected for optical characterization and stability study. Figure 5 shown.

[0078] 0.5 g of (BACQ)2MnCl4 crystals were immersed in 1 mL of different organic solvents: methanol (MeOH), isopropanol (i-PrOH), ethyl acetate (EtOAc), toluene (Toluene), dioxane (Dioxane), n-hexane (Hexane), tetrahydrofuran (THF), acetone (Acetone), acetonitrile (CH3CN) and concentrated hydrochloric acid (HCl). After immersion for 10 days, luminescence test was carried out.

[0079] Depend on Figure 5As shown in (a), compared with the first day (not immersed), the (BACQ)2MnCl4 crystals can still emit strong green light under 365nm ultraviolet excitation after continuous immersion for 10 days, indicating that the (BACQ)2MnCl4 crystals have high corrosion resistance to polar organic solvents and acidic solutions.

[0080] Depend on Figure 5 As can be seen from (b) in the figure, compared with the unsoaked (BACQ)2MnCl4 crystals, the fluorescence spectrum intensity of the (BACQ)2MnCl4 crystals only showed a slight decrease after being continuously soaked in different solvents for 10 days, further confirming that the crystals still have good stability in organic solvents and acidic solutions.

[0081] Further, by Figure 5 As shown in (c), after immersion in concentrated hydrochloric acid for 10 days, the fluorescence intensity of (BACQ)2MnCl4 crystals only decreased by 13.6%. Despite long-term immersion in various organic solvents and acidic aqueous solutions, the powder X-ray diffraction spectrum of (BACQ)2MnCl4 crystals is basically consistent with the original spectrum of (BACQ)2MnCl4 crystals without immersion, as shown in Figure 2. Figure 5 As shown in (d), this further proves that the crystal has excellent stability and acid corrosion resistance.

[0082] In addition, the stability of (BACQ)2MnCl4 crystals under various conditions, such as atmospheric exposure, light, and heating, was also tested. Compared with the newly prepared (BACQ)2MnCl4 crystals, the fluorescence intensity did not decrease significantly under the laboratory environment of atmospheric exposure for 30 days (e) and light exposure for 48 hours (f); when the (BACQ)2MnCl4 crystals were heated at 150°C for 48 hours (h), the fluorescence intensity of the (BACQ)2MnCl4 crystals decreased slightly.

[0083] Powder X-ray diffraction characterization was performed on (BACQ)2MnCl4 crystals that were exposed to the atmosphere in a laboratory environment for 30 days, exposed to light for 48 hours, and heated at 150°C for 48 hours (g). The diffraction patterns did not show significant differences compared to the freshly prepared (BACQ)2MnCl4 crystals.

[0084] The above results show that (BACQ)2MnCl4 crystals still have good stability under atmospheric exposure, light and heating conditions.

[0085] 4. Effect of cations on the half-peak width and stability of crystals

[0086] In addition, in order to further study the narrow half-width characteristics of the crystal, the emission spectra of the (BACQ)2MnCl4 crystal of Example 1 and the (BACQ)2MnBr4 crystal of Example 2 were investigated in the range of 80K to 300K as a function of temperature.

[0087] Depend on Figure 6 From (a) and (b), we can see that in the range of 80K-300K, the highest wavelength peaks of (BACQ)2MnCl4 crystal and (BACQ)2MnBr4 crystal have nothing to do with temperature. Figure 6 As shown in (a), when the temperature rises from 80K to 200K, the luminescence intensity of (BACQ)2MnCl4 crystal begins to increase, and then decreases as the temperature approaches room temperature. This change pattern is consistent with Figure 6 The photograph shown in (c) shows the same. However, the temperature-dependent emission spectrum of (BACQ)2MnBr4 is different from that of (BACQ)2MnCl4 crystal. As the temperature increases, the luminescence intensity of (BACQ)2MnBr4 crystal decreases, which is mainly caused by the increase of non-radiative transitions.

[0088] In addition, the relationship between the half-peak width and temperature was analyzed according to the following formula to evaluate the electron-phonon coupling of (BACQ)2MnBr4 crystals:

[0089]

[0090] Where FWHM is the half maximum width, T is the temperature, ω is the phonon frequency, is the Plank constant, S is the Huang-Rhys factor, k B is the coefficient.

[0091] The calculated Huang-Rhys factor (S) of the (BACQ)2MnBr4 crystal is 6.34, which indicates that the interaction between electrons and phonons in the 0D (BACQ)2MnBr4 lattice is weak, thus verifying the rigidity of the crystal structure and the characteristics of narrow fluorescence emission.

[0092] The crystal structure was further analyzed to study the effect of cations on the narrow half-width and stability of the peak. Figure 6 From (d) in (BACQ)2MnBr4, we can see that [BACQ] + The conjugated quinoline groups of the cation exhibit parallel π…π stacking. Figure 6 From (e) in the figure, it can be seen that the -CH3 group and the quinoline group are and The bond length forms a CH…π hydrogen bond.

[0093] In order to further analyze the interaction between molecules, CrystalExplorer software was used to calculate the radius of The energies of the crystal cations in the range of 2.4.2 ... Figure 6 (f) is shown. The Hirshfeld surface of (BACQ)2MnBr4 crystal was analyzed. Figure 6 As shown in (g), the Hirshfeld surface diagram shows that there is a CH…π relationship between the hydrogen atom and the quinoline ring.

[0094] Therefore, it can be concluded that [BACQ] + The π…π stacking and CH…π hydrogen bonding of the cations promote the rigidity of the crystal structure, which is beneficial for narrow-band emission and crystal stability. The total energy framework was evaluated to further verify this conclusion. Figure 6 (h) clearly shows the total energy framework of the (BACQ)2MnBr4 crystal along the c-axis. The larger the radius of the cylinder connecting the molecular center of mass, the higher the interaction energy and the more stable the crystal.

[0095] 5. Application

[0096] Crystals with extremely narrow half-peak width and stability are excellent choices for manufacturing optical devices. Since the (BACQ)2MnBr4 crystal of Example 2 has the narrowest half-peak width, this crystal is selected to assemble LEDs.

[0097] By coating a layer of (BACQ)2MnBr4 crystal and commercially available K2SiF6:Mn on the blue chip 4+ Red phosphor (KSF) produces white light LEDs with a color temperature of 7160K, such as Figure 7 (a) shown.

[0098] Depend on Figure 7 As can be seen from (b) in FIG. 1 , the CIE coordinates of the white light LED emission spectrum are (0.301, 0.312) and the color gamut is wide, reaching 105% of the NTSC 1931 standard.

[0099] In order to study the emission spectrum of (BACQ)2MnBr4 crystal with current variation, the emission spectrum of the white light LED at different operating currents was measured. Figure 7 (c) Figure 7 (c) Arrange Figure 7 (d) It can be seen that the intensity of the emission spectrum increases linearly with the increase of the working current.

[0100] And, by Figure 7As shown in (e), the white light LED can still maintain high efficiency after working for 24 hours, showing excellent working stability.

[0101] The above results indicate that the (BACQ)2MnBr4 crystal of Example 2 has considerable application potential in the field of LED displays and lighting.

[0102] In addition, the (BACQ)2MnBr4 crystals of Example 2 were also used on the polymer film. Figure 7 As shown in (f), a polymer material, such as polymethyl methacrylate, is dissolved in dichloromethane, and then ground powdered (BACQ)2MnBr4 crystals are added. After evaporation and drying, a flexible polymer film is obtained. This flexible material has application potential in wearable optoelectronic devices.

Claims

1. A stable manganese-based halide with narrow-band green light emission, characterized in that: The manganese-based halide is (C 13 H 16 ClN2)2MnX4, where (C 13 H 16 ClN2) + is a 1-hydrogen-4-butylamino-7-chloroquinoline cation, and X is Cl or Br; The 13 H 16 ClN2)2MnCl4 belongs to the monoclinic system, and its space group is C 2 / c ; The 13 H 16 ClN2)2MnBr4 belongs to the triclinic system, and its space group is P ī; In the manganese-based halide, all Mn 2+ All of them are coordinated with four halogen atoms to form 0D [MnX4] 2- Tetrahedral structure; The manganese-based halide is prepared by the following steps: (1) Synthesis of 4-butylamino-7-chloroquinoline: Under nitrogen protection, 4,7-dichloroquinoline and n-butylamine are mixed, heated to reflux and then cooled, sodium hydroxide solution is added, stirred, and the precipitated solid is filtered, washed, dried, and purified to obtain 4-butylamino-7-chloroquinoline; (2) preparing a manganese-based halide: uniformly mixing a manganese-containing halide, 4-butylamino-7-chloroquinoline, propylene glycol and an acidic solvent, evaporating the solvent to precipitate crystals, washing and drying to obtain a manganese-based halide; In the step (2), a manganese-based halide is prepared. If the manganese-based halide is (C 13 H 16 ClN2)2MnCl4, then the manganese-containing halide is manganese chloride and the acidic solvent is hydrochloric acid; If the manganese-based halide is (C 13 H 16 ClN2)2MnBr4, then the manganese-containing halide is manganese bromide and the acidic solvent is hydrobromic acid; In the step (2), the molar ratio of the manganese halide to 4-butylamino-7-chloroquinoline is 1:2; the volume ratio of propylene glycol to the acidic solvent is 4:3; and the molar ratio of the manganese halide to the acidic solvent is 0.2 mmol:72 mmol.

2. The narrow-band green light emitting stable manganese-based halide according to claim 1, characterized in that: The 13 H 16 ClN2)2MnCl4, emits 526nm green light under 369nm ultraviolet light excitation, with a half-peak width of 55nm; The 13 H 16 ClN2)2MnBr4, emits 519nm green light under 370nm ultraviolet light excitation, with a half-peak width of 39nm.

3. Use of the stable manganese-based halide with narrow-band green light emission as claimed in claim 1 or 2 in fluorescent materials.

4. The use according to claim 3, characterized in that: Application of the manganese-based halide in optical devices.

5. The use according to claim 4, characterized in that: The manganese-based halide is used to improve the color gamut and stability of optical devices.

Citation Information

Patent Citations

  • Nitrogen-containing amphiphilic organic ion manganese halide luminescent material as well as preparation method and application thereof

    CN112521287A

  • Mn-based organic-inorganic hybrid metal halide luminescent material and preparation method thereof

    CN114656364A